Rapid Alert System for Food and Feed (RASFF) 2009-2016 Turkey Report - Selin Çınar; Sevda Nur Yılmaz; Ecem Aydın; Aslı Yorulmaz (Turkish Journal of Agriculture: Food Science and Technology)
RASFF (Rapid Alert System for Food and Feed) is an international system, that provides the rapid information exchange between European Union countries towards risks about food and feed topics, takes the required precautions and thus aims to maintain the food and feed safety. The weekly reports sent by member countries, are presented on web site and the member countries are informed in case of a risk when the product is introduced in the market. The current work includes the notifications originated from our country that took place in rapid alert system reports between years 2009-2016. The data obtained from the system, were classified according to product and hazard groups and the product-hazard relations were evaluated for each year by taking the notification types into consideration. According to the assessments, the main problem about European Union exports of our country is the high aflatoxin level of the products. This problem is mainly observed in fruits-vegetables, nuts and seeds. Pesticide residues and pathogenic microorganisms are the other important hazard groups which cause problems for exports of our country. The results obtained from the current work are critically important for determination of the basic problems met in food export of our country and to capture attention to precautions which should be taken against those problems.